2018
DOI: 10.1007/s10278-018-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Mapping of CT Scan Locations on Computational Human Phantoms for Organ Dose Estimation

Abstract: To develop an algorithm to automatically map CT scan locations of patients onto computational human phantoms to provide with patient-specific organ doses. We developed an algorithm that compares a two-dimensional skeletal mask generated from patient CTs with that of a whole body computational human phantom. The algorithm selected the scan locations showing the highest Dice Similarity Coefficient (DSC) calculated between the skeletal masks of a patient and a phantom. To test the performance of the algorithm, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The ImPACT CT patient dosimetry calculator estimates organ‐level absorbed doses and effective dose based on spreadsheet tools and adult stylized phantoms . Although this approach is practical, it is impaired by the dosimetric uncertainties resulting from the large differences between the anatomy of patients and simulated computational phantoms (categorized by gender and age) in addition to the inherent uncertainties associated with protocol‐based mapping of the scan location on the computational models . Since Monte Carlo calculations using patient‐specific models are commonly considered as reference for organ dose estimation from diagnostic imaging procedures, the implementation of an easy to use and reliable framework enabling to estimate patient‐specific organ dose for individual patients in clinical setting is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The ImPACT CT patient dosimetry calculator estimates organ‐level absorbed doses and effective dose based on spreadsheet tools and adult stylized phantoms . Although this approach is practical, it is impaired by the dosimetric uncertainties resulting from the large differences between the anatomy of patients and simulated computational phantoms (categorized by gender and age) in addition to the inherent uncertainties associated with protocol‐based mapping of the scan location on the computational models . Since Monte Carlo calculations using patient‐specific models are commonly considered as reference for organ dose estimation from diagnostic imaging procedures, the implementation of an easy to use and reliable framework enabling to estimate patient‐specific organ dose for individual patients in clinical setting is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reported that general scan protocols are not always strictly followed [46] even in a clinical trial where protocols are carefully designed and provided to participating hospitals. To avoid dose errors caused by a disagreement between a patient and phantom, automatic mapping methods have been investigated [52] that compare patient CT images with predefined anatomical landmarks in computational human phantoms to map the locations of scan start and end of a patient on those of phantoms. Machine learning could be used for mapping organs from CT images to computational human phantoms [53].…”
Section: Ongoing and Future Researchmentioning
confidence: 99%
“…However, large differences between the anatomy of patients and computational phantoms may cause nonnegligible uncertainties in radiation dosimetry. 26 Delineation of the target volume and organs at risk from patient-specific images are commonly used in radiation treatment planning, 27 where CT numbers are converted into material properties 12 and voxel-based radiation dosimetry can be obtained through Monte Carlo simulations. A voxel dose map combined with automatic organ segmentation can achieve high accuracy in dosimetry with clinically acceptable speed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, habitus‐dependent phantom series 22–24 and deformable computational phantoms 25 have been developed to represent individual patients for radiation dose estimation. However, large differences between the anatomy of patients and computational phantoms may cause non‐negligible uncertainties in radiation dosimetry 26 …”
Section: Introductionmentioning
confidence: 99%